Health and well-being of rotation workers in the mining, offshore oil and gas, and construction industry: a systematic review. Issue 7 (23rd July 2021) - Asare, Bernard Yeboah-Asiamah; Kwasnicka, Dominika; Powell, Daniel; Robinson, Suzanne
Abstract : Introduction: Rotation work, characterised by travelling long distances to work in isolated areas where workers typically rotate consecutive days working and living on-site with periods at home, is increasingly used in the resources and construction sectors globally. Such employment practices may have an impact on workers' health and well-being. This systematic review explores the impact rotation work has on mental and physical outcomes in rotation workers in the resources and construction sectors. Method: The PubMed, Medline, EMBASE, CINAHL, PsycINFO, and Scopus databases were systematically searched on 1 May 2020 to identify quantitative, qualitative and mixed-method studies addressing the health of rotation workers published in peer-reviewed journals. Findings from the studies were summarised narratively. Results: Of 6268 studies retrieved, 90 studies were included in the review. Studies suggested higher prevalence of psychological distress in onshore rotation workers and higher overweight/obesity rates among rotation workers as compared with the general population. We found more sleep problems and higher levels of smoking during work periods compared with off-site days; and higher alcohol intake during off-site days compared with on-site days. Workers generally perceived their physical health status as good. High-perceived job demands (such as workload, repetitive work) were associated with mental distress and exhaustion, sleep problems and perceived poor physical health status, while high-perceived job resources (such as job clarity/control, support) were associated with low mental distress and exhaustion, less smoking and alcohol intake, and better sleep. Conclusion: Rotation work is associated with several poorer health behaviours and outcomes, such as sleep problems, smoking, alcohol consumption and overweight/obesity. Interventions needed to improve rotation workers' health should include maximising available job resources and reducing job demands. Further longitudinal studies are needed to explore the long-term health effects of rotation work and the short-term contextual effects of the different aspects of rotation work.